2007
DOI: 10.4197/met.18-2.7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Fungal Communities Associated with Litter of Plant Cover at Al-Taif Province, Saudi Arabia

Abstract: Twenty one fungal species belonging to ten genera were isolated from the litter of eight dominant plants cover of Al-Taif province, Saudi Arabia. The most frequently isolated fungal species were Fusarium oxysporum (100%), Aspergillus alutaceus, A. niger, and Macrophomina phaseolina (87.5%), F. solani, Mucor racemosus, Penicillium glaburum (75%), and P. jaczewskii (62.5%). The influence of temperature and pH on selected eleven isolates, representing the dominant fungal species, was estimated. The representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…It is worthy to mention that literatures dealing with isolation and identification of fungi from Yemeni plant residues are rare. In this respect, In Al-Taif province, Saudi Arabia, Kabli, (2007), screened the presence of mycoflora in the samples of the litters of some plants which contained deciduous leaves, twigs, flowers, seeds, fruits and plant bark, beside other dead plant materials. He identified twenty one fungal species belonging to ten different genera of which F. oxysporum was dominant followed by A. niger, F. solani, M. racemosus, P. glabrum and P. janczewskii.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worthy to mention that literatures dealing with isolation and identification of fungi from Yemeni plant residues are rare. In this respect, In Al-Taif province, Saudi Arabia, Kabli, (2007), screened the presence of mycoflora in the samples of the litters of some plants which contained deciduous leaves, twigs, flowers, seeds, fruits and plant bark, beside other dead plant materials. He identified twenty one fungal species belonging to ten different genera of which F. oxysporum was dominant followed by A. niger, F. solani, M. racemosus, P. glabrum and P. janczewskii.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, Kabli, (2007), found that Acremonium strictum, A. flavipes, A. niger, Emericella nidulans, Gliocladium roseum, M. racemosus and P. janczewskii , were capable of producing cellulolytic, pectinolytic and amylolytic enzymes, which indicated their major role in litter decomposition. Said, et al, (1991), showed that P. frequentans produced high levels of extracellular pectinases.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…La determinación de la densidad relativa (DR) y la frecuencia relativa (FR) de las colonias en el aire y en polvo se realizó según Smith [20], Esquivel et al [21] y Saleh [22], respectivamente.…”
Section: Identificación De Los Aisladosunclassified